Identification of Toxocara spp., and Strongyloides spp, Hunting Dogs in the Kamuyang River Kenagarian, Luak District, Limapuluh Kota Regency - Putri, Ilviga Anggraini; Zelpina, Engki .; Suliha; Latisar (Media Kedokteran Hewan, 2023)
This study was conducted on hunting dogs in Kanagarian Sungai Kamunyang, Luak District, Limapuluh Kota Regency. The purpose of this study was to identify Toxocara spp., and Strongyloides spp., and to determine the prevalence of worm infection in hunting dogs. This research is an observational study conducted by cross sectional. Samples were taken as many as 50 hunting dog feces and examined using the floating test method. The results of this study found that from 50 hunting dogs whose feces samples were taken, 30 samples of feces were identified as infected by Toxocara spp., 3 samples and Strongyloides spp., 14 samples. The conclusion of this study was that hunting dogs in the Kanagarian Sungai Kamunyang were infected with Toxocara spp., 6%, Strongyloides spp., 28%.